Influence of feeding bee colonies on colony strenght and honey authenticity - Andreja KANDOLF BOROVŠAK; Nives OGRINC; Nataša LILEK; Boštjan NOČ; Janko BOŽIČ; Mojca KOROŠEC (Acta Agriculturae Slovenica, 2015)
For the natural development of bee colonies, there is the need for appropriate nutrition. Lack of natural honey flow must be supplemented by feeding bee colonies with sugar syrups or candy paste. This supplementary feeding encourages brood breeding and forage activity, whereby stronger colonies collect more honey. Sugar syrups can cause honey adulteration, which is more frequent with the reversing of the brood combs with the bee food, with the combs moved from the brood chamber to the upper chamber. Authentication of honey from the standpoint of the presence of sugar syrup is very complex, because there is no single method by which honey adulteration can be reliably confirmed. Feeding the colonies in spring should result in stronger colonies and hence the collection of more honey in the brood chambers. The objective of the present study was to determine whether this has effects also on honey authenticity, and to discover a simple method for detection of honey adulteration. The colonies were fed with candy paste that had added yeast and blue dye, to provide markers for detection of honey adulteration. The strength of the colonies and quantity of honey in the brood chambers were monitored. The results of the analysis of stable isotope and activity of foreign enzymes were compared with the results of yeast quantity and colour of the honey (absorbance, L*, a*, b* parameters). Detection of yeast in the honey samples and presence of colour as a consequence of added dye appear to be appropriate methods to follow honey adulteration, and further studies are ongoing.